10 Vortex formation time: a novel differentiator between physiological and pathological cardiac adaptation. (28th September 2016) - Cuddy, S; King, G; Bajrangee, A; Murphy, R; Daly, C
Abstract : Introduction: Elite athletes undertake endurance training that can lead to increased left ventricular wall thickness thus creating uncertainty regarding the differential diagnosis of athlete's heart from hypertrophic cardiomyopathy (HCM). The distinction of physiological from pathological LV wall hypertrophy is crucial because of the risk of sudden cardiac death associated with HCM. Vortex formation time (VFT) is a novel index of biological fluid transport efficiency. It is a dimensionless index of the left ventricular filling that integrates all phases of diastole (T≈ 4 (3.3–5.5)). It has been shown to reliably differentiate between healthy control subjects and heart failure patients. We hypothesised that VFT can be used to differentiate between physiological and pathological cardiac adaptation, especially in this challenging population of "athletes heart" versus mild hypertrophic cardiomyopathy. Methods: We compared echocardiographic indices between 41 elite male strength endurance athletes with mild symmetrical LVH, 11 male patients with a mild phenotype of hypertrophic cardiomyopathy against 20 sedentary volunteers (age, weight and sex-matched). VFT was obtained using the validated formula: 4 × (1 − β )/ π × α ³ × LVEF, wheris the fraction of total transmitral diastolic stroke volume contributed by atrial contraction and α is the biplane end-diastolic volume (EDV) 1/3 divided by mitral annular diameter during early diastole. Multiple regression analysis was used to adjust for heart rate and age. Results: There was no difference in gender and body surface area between the controls, athletes and hypertrophic cardiomyopathic patients. Septal wall thickness was 1.4 cm ± 0.1 in the HCM group compared to 1.3 cm ± 0.1 in the athletes and 0.89 cm ± 0.2 in the controls. The heart rate was 63 ± 10 bpm in the athletes vs. 74 ± 7 bpm in sedentary controls and 81 ± 4 bpm in HCM group (p = 0.001). The VFT was highest in the athletic group, lower in the sedentary group and lowest in the HCM group (4.01 ± 0. 80 vs. 3.12 ± 0.38 vs. 2.5 ± 0.8) (p < 0.001). Conclusion: The VFT was normal in endurance Rowers and controls but significantly reduced below the optimal value in the hypertrophic cardiomyopathy patients. We conclude that pathological left ventricular hypertrophy (LVH) can be differentiated from physiological LVH by the presence of decreased Vortex formation time. Vortex formation time is a new useful differentiator between pathological and physiological LVH to guide physicians decision making in this challenging population.